Marketing Mix Implementation on Products, Prices, Places, Promotions In Marketing of Education Services - Nurman, Amril; Harapan, Edi (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2021)
This article aims to describe the implementation of the marketing mix in product, price, place and promotion in the marketing of educational services.